The proportion and characteristics of hypertension outpatients in productive age at Selemadeg Public Health Center, Tabanan in 2020 - Made Dyah Vismita Indramila Duarsa Duarsa; Hanik Nuryanti; Yenny Kandarini; Gede Wira Mahadita; Putu Aryani; Bagus Juniada (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2020)
Background: Selemadeg Public Health Center (PHC) had reported, in 2018, hypertension is still included as the top 10 diseases within its community care area. The last registration data showed that mostly hypertension cases was still related to productive age population. Aims: This study aims to assess the incidence of hypertension in preventing the risk factors of hypertension. Method: This research was conducted at Selemadeg PHC, Tabanan in the period of time between February-March 2020, using a descriptive study form with a consecutive sampling technique. Results: It indicated that 33.3% from all patients had experienced hypertension. Based on gender, more in female respondents, on the rate of 41.7%. Based on the family history, it was found that 50.0% of them have had a family history of hypertension. Based on the obesity status, 55.6% with a BMI> 25. Based on high salt consumption was found 50.0% and based on low physical activity was 37,9% on smoking habits 44.4% indicated that the patient was a smoker. Conclusion: The proportion of hypertension involved productive age patients as well as it was found more in the female gender group, with a family history of hypertension, high salt consumption, smokers, obesity and has a low physical activity pattern.